Mechanisms of complex regional pain syndrome - Devarajan, Jagan; Mena, Shayla; Cheng, Jianguo (Frontiers in Pain Research, 2024)
Complex Regional Pain Syndrome (CRPS) is a chronic pain disorder characterized by a diverse array of symptoms, including pain that is disproportionate to the initial triggering event, accompanied by autonomic, sensory, motor, and sudomotor disturbances. The primary pathology of both types of CRPS (Type I, also known as reflex sympathetic dystrophy, RSD; Type II, also known as causalgia) is featured by allodynia, edema, changes in skin color and temperature, and dystrophy, predominantly affecting extremities. Recent studies started to unravel the complex pathogenic mechanisms of CRPS, particularly from an autoimmune and neuroimmune interaction perspective. CRPS is now recognized as a systemic disease that stems from a complex interplay of inflammatory, immunologic, neurogenic, genetic, and psychologic factors. The relative contributions of these factors may vary among patients and even within a single patient over time. Key mechanisms underlying clinical manifestations include peripheral and central sensitization, sympathetic dysregulation, and alterations in somatosensory processing. Enhanced understanding of the mechanisms of CRPS is crucial for the development of effective therapeutic interventions. While our mechanistic understanding of CRPS remains incomplete, this article updates recent research advancements and sheds light on the etiology, pathogenesis, and molecular underpinnings of CRPS.